Comparative Study of Beta-Blockers Versus Calcium Channel Blockers in the Management of Stable Angina in Elderly Patients - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stable angina is a common clinical manifestation of coronary artery disease in the elderly population. Age-related physiological changes, polypharmacy, and comorbidities often complicate its management. Beta-blockers and calcium channel blockers (CCBs) are widely used anti-anginal agents; however, limited comparative data exist specifically for elderly cohorts regarding their efficacy and safety profiles. Objective: To compare the clinical efficacy and safety of beta-blockers versus calcium channel blockers in elderly patients with stable angina. Methods: This prospective, comparative cross-sectional study included 100 patients aged 65 years or older with a confirmed diagnosis of stable angina. Patients were recruited from the cardiology departments of Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Mayo Hospital, Lahore, between April 2022 and April 2023. Participants were divided into two equal groups: Group A received beta-blockers (metoprolol or bisoprolol) and Group B received calcium channel blockers (amlodipine or diltiazem). Clinical assessments were conducted at baseline, 6 weeks, and 12 weeks, evaluating angina episode frequency, CCS class improvement, exercise tolerance (treadmill test), resting heart rate, blood pressure, and adverse drug events. Statistical analysis was performed using SPSS version 26.0, with a p-value <0.05 considered significant. Results: Both treatment groups demonstrated significant clinical improvement over the 12-week period. The mean angina episodes per week were lower in Group A (2.1 ± 0.9) compared to Group B (2.4 ± 1.1), though not statistically significant (p=0.18). CCS class improvement by at least one grade occurred in 76% of Group A and 68% of Group B patients (p=0.37). Group A showed a slightly longer mean exercise duration (7.8 ± 1.6 vs. 7.3 ± 1.5 minutes; p=0.09) and a delayed time to onset of angina. Resting heart rate was significantly lower in Group A (65.6 ± 6.8 bpm) than in Group B (72.4 ± 7.3 bpm; p<0.001). Peripheral edema occurred more frequently in Group B (16%) versus Group A (4%; p=0.04), while fatigue was reported slightly more in Group A (20% vs. 12%; p=0.27). Drug discontinuation due to side effects was low in both groups. Conclusion: Both beta-blockers and calcium channel blockers are effective and well-tolerated treatments for stable angina in elderly patients. Beta-blockers offer better heart rate control and slight improvement in exercise tolerance, whereas CCBs remain suitable alternatives for patients with contraindications to beta-blockers. Individualized therapy selection based on comorbidities, hemodynamic parameters, and side-effect profiles is essential for optimizing outcomes in this high-risk population. Keywords: Angina, Beta-blockers, Calcium-channel-blockers, Elderly, Exercise, Heart-rate, Pharmacotherapy